Optimizing Performance Through Commitment - Putri Tampubolon, Dionica; Isa Indrawan, Muhammad (PT. Multidisciplinary Press Indonesia, 2025)
This research aims to analyze the influence of work culture and competency on employee performance with commitment as an intervening variable at BPJS Employment Branch Offices throughout Medan Raya. A quantitative approach was used in this research, with data collection through questionnaires distributed to employees as respondents. The data analysis technique uses the Partial Least Square (PLS) method to test direct and indirect relationships between research variables. The results of this research are as follows: Work Culture has a positive and significant effect on Employee Performance with an original sample value of 0.267 and a p value of 0.002. Work Culture has a positive and insignificant effect on Commitment with an original sample value of 0.110 and a p value of 0.153. Commitment has a positive and significant effect on Employee Performance with an original sample value of 0.298 and a p value of 0.016. Competency has a positive and significant effect on employee performance with an original sample value of 0.370 and a p value of 0.012. Competence has a positive and significant effect on Commitment with an original sample value of 0.804 and a p value of 0.000. Work Culture has a positive and insignificant effect on employee performance through Commitment with an original sample value of 0.033 and a p value of 0.173. Competence has a positive and insignificant effect on employee performance through Work Commitment with an original sample value of 0.240 and a p value of 0.027.